Response of Peanut due to Application of Dolomite Plus - Sutriadi, Mas Teddy; Setyorini, Diah (JOURNAL OF TROPICAL SOILS, 2012)
Most developing areal for peanut crop (Arachis hoypogeae) is upland, that is dominated by parent soil and has acidcharacteristis. Main constraints for this soil are pH and low soil productivity. Dolomite plus is a dolomite ameliorant,with phosphate nutrient. The dolomite plus beside as the ameliorant and a source of magnecium and calciumnutrients, also as a source of phosphate nutrient. The objective of the research was to study effectivity of dolomiteplus on peanut growth in Inceptisols soil. This research was conducted in the greenhouse using a randomizecompletely designed with 8 treatments and 5 replications. The treatments were control, NPK, and combinations ofNPK with six dolomite plus levels. Relative Agronomic Effectiveness (RAE) analyses was used determine to theeffectivity of dolomite plus. The result showed that application of dolomite plus 1,600 kg ha-1 with NPK fertilizerincreased dry weight of grain yield untill 27% (11.53 to 14.65 g plant-1) compared to NPK fertilizer application alone,that was showed by RAE > 100% or among 171-251%. Application of dolomite plus with NPK increased soil pH, soilavailable P (Bray 1), Ca and Mg exchangeable, and CEC as 1.9 unit; 6.2 mg kg-1; 15.87 cmol(+) kg-1; 14.27 cmol(+)kg-1; and 17.29 cmol(+) kg-1 respectively. Maximum rate of dolomite plus was 2,500 kg ha-1 with the yield was 14.2 gplant-1 grain dry weight. The rate of dolomite plus that was higher than 2,500 kg ha-1 could decrease the yield[How to Cite: Sutriadi MT and D Setyorini. 2012. Response of Peanut due to Application of Dolomite Plus. J Trop Soils 17: 143-150. Doi: 10.5400/jts.2012.17.2.143]Â [Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.143]